2015
DOI: 10.1162/jocn_a_00803
|View full text |Cite
|
Sign up to set email alerts
|

Attention and Temporal Expectations Modulate Power, Not Phase, of Ongoing Alpha Oscillations

Abstract: Abstract■ The perception of near-threshold visual stimuli has been shown to depend in part on the phase (i.e., time in the cycle) of ongoing alpha (8-13 Hz) oscillations in the visual cortex relative to the onset of that stimulus. However, it is currently unknown whether the phase of the ongoing alpha activity can be manipulated by top-down factors such as attention or expectancy. Using three variants of a cross-modal attention paradigm with constant predictable stimulus onsets, we examined if cues signaling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 47 publications
8
105
0
Order By: Relevance
“…Similar approaches were used by Osipova et al (2006), Jokisch and Jensen (2007), Mazaheri et al (2009), and Van Diepen et al (2015). Although this approach uses a smaller number of cycles in comparison to Morlet wavelet approaches of time frequency decompositions (i.e., 5–7 cycles); it does afford the maximum temporal resolution for pre-and-post fluctuations in alpha power.…”
Section: Methodsmentioning
confidence: 99%
“…Similar approaches were used by Osipova et al (2006), Jokisch and Jensen (2007), Mazaheri et al (2009), and Van Diepen et al (2015). Although this approach uses a smaller number of cycles in comparison to Morlet wavelet approaches of time frequency decompositions (i.e., 5–7 cycles); it does afford the maximum temporal resolution for pre-and-post fluctuations in alpha power.…”
Section: Methodsmentioning
confidence: 99%
“…The control serves to phase-synchronize the oscillations between different regions and modulate the degree of pulsed inhibition to allocate computational resources. A number of studies have shown that alpha magnitude and phase can be modulated in anticipation of relevant or irrelevant stimuli (Foxe et al, 1998; Thut et al, 2006; Foxe and Snyder, 2011; Bonnefond and Jensen, 2012; Samaha et al, 2015; but see van Diepen et al, 2015), indicating that alpha oscillatory activity is indeed under internal control. In this section, we discuss two complementary mechanisms for this control, namely that alpha oscillations are controlled by neocortical feedback connections or by the thalamus.…”
Section: Control Of Alpha Oscillations In Relation To Cortical Layersmentioning
confidence: 99%
“…Recent experiments show that the brain can either actively adjust its alpha phase during an attentional distractor task [28,29] or modulate the power [30]. These studies have focused on alpha phase adjustments in tasks with temporal expectations about the onset of stimuli.…”
Section: Introductionmentioning
confidence: 99%